Kyrgyz Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments in the Kyrgyz Republic during the 1990s. The cash fiscal deficit increased from 7.7 percent of GDP in 1994 to 12.5 percent of GDP in 1995. The authorities encountered difficulties in raising revenues early in the year, but with the implementation of measures to strengthen tax collection, taxes were maintained at about 13.5 percent of GDP for the year as a whole. However, total budget revenues fell from 21 percent of GDP in 1994 to 16 percent of GDP in 1995, reflecting a sharp decline in central bank profit transfers and food grants.